Linking managers' emotional intelligence, cognitive ability and firm performance: Insights from Vietnamese firms - Huong Trang Kim (Cogent Business & Management, 2020)
The objective of our paper is to explore the impact of managers' emotional intelligence (EQ) and cognitive ability (IQ) on firm performance. In this regard, an experimental survey on managers from 623 textile and garments firms in Vietnam was conducted. We applied the International Positive Affectivity-Negative Affectivity Schedule-short form (I-PANAS-SF) to measure EQ, and Cognitive Reflection test (CRT) to measure IQ. We find that both emotional intelligence and cognitive ability matter with firm performance. One unit increase in a manager's EQ leads to a 18.3 percentage point increase in firm performance. Likewise, a firm whose manager has higher IQ performs better. IQ also enhances the effect of a manager's education on firm performance. An interesting finding of this study is that the effect of EQ on firm performance is more significant among male than female managers. From a managerial standpoint, the findings of our study suggest that to improve firm performance, it may be beneficial for organizations to recruit, facilitate and promote emotionally intelligent managers who have good cognitive ability and managerial skills.
Keywords: G41; D22; D91; 650; emotional intelligence; cognitive ability; firm performance; experimental survey; managers